Type Ia (spherical) communicating colonic duplication in a dog treated with colectomy. (30th January 2017) - Fernandez, N.; Morrison, L.; Liuti, T.; Frame, M.; Yool, D.
Abstract : A six‐month‐old Labrador retriever presented for investigation of a colonic mass identified as an incidental finding during exploratory coeliotomy. Computed tomography identified a lesion in the colon which occupied part of its lumen and shared blood supply with the remainder of the colon. The lesion was suspected to be a colonic duplication and it was excised by segmental colectomy during exploratory coeliotomy. Histopathology from the excised colon confirmed the diagnosis of a colonic duplication. The dog recovered uneventfully and had no complications. To the authors' knowledge, this is the first report of an asymptomatic, spherical, communicating colonic duplication and the first report to describe segmental colectomy for the management of this condition in veterinary patients.